2022
DOI: 10.17269/s41997-022-00621-z
|View full text |Cite
|
Sign up to set email alerts
|

“None of it was especially easy”: improving COVID-19 vaccine equity for people with disabilities

Abstract: Objectives Our study aimed to (1) identify barriers to equitable access to COVID-19 vaccines for Canadians with disabilities and (2) present recommendations made by study participants to improve immunization programs in terms of inclusivity and equitable access. Methods We invited Manitobans living with disabilities to participate in online focus groups. Focus groups were conducted across multiple disability experiences, although one focus group was advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
0
12
0
1
Order By: Relevance
“…For some respondents, this could be related to concerns around vaccine service accessibility; approximately 8% of survey respondents indicated that improved vaccine service accessibility for all abilities would be important for making vaccination easier. To ensure those who plan to receive additional vaccine doses are able to act on their intentions, and facilitate uptake in those who are undecided, vaccine services must consider the needs of all abilities [27], and involve those who live with disabilities in service planning [28]. Improved understanding of potential barriers to vaccine uptake in this population is also required [29].…”
Section: Discussionmentioning
confidence: 99%
“…For some respondents, this could be related to concerns around vaccine service accessibility; approximately 8% of survey respondents indicated that improved vaccine service accessibility for all abilities would be important for making vaccination easier. To ensure those who plan to receive additional vaccine doses are able to act on their intentions, and facilitate uptake in those who are undecided, vaccine services must consider the needs of all abilities [27], and involve those who live with disabilities in service planning [28]. Improved understanding of potential barriers to vaccine uptake in this population is also required [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with physical disabilities, homebound or bedbound, may have been unable to go to the vaccination centers. Physical access to vaccination clinics has been identified as a potential barrier to COVID-19 vaccination ( 41 ). Arranging transportation and other infrastructural enhancement at the vaccination sites are recommended to improve accessibility to people with disabilities ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical access to vaccination clinics has been identified as a potential barrier to COVID-19 vaccination ( 41 ). Arranging transportation and other infrastructural enhancement at the vaccination sites are recommended to improve accessibility to people with disabilities ( 41 ). The Singapore government organized outreach programmes like mobile vaccination teams and home vaccination schemes to address limitations to access ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure those who plan to receive additional vaccine doses are able to act on their intentions, and facilitate uptake in those who are undecided, vaccine services must consider the needs of all abilities (27), and involve those who live with disabilities in service planning. (28) Improved understanding of potential barriers to vaccine uptake in this population is also required. (29) Our results indicated both concerning and encouraging relationships between sociodemographic factors and additional vaccine dose acceptance.…”
Section: Discussionmentioning
confidence: 99%